Well‐Defined Fullerene Bisadducts Enable High‐Performance Tin‐Based Perovskite Solar Cells. Issue 9 (4th January 2023) - Sun, Chao; Yang, Panpan; Nan, Ziang; Tian, Chengbo; Cai, Yuanting; Chen, Jingfu; Qi, Fangfang; Tian, Hanrui; Xie, Liqiang; Meng, Lingyi; Wei, Zhanhua
Abstract: Tin‐based perovskite solar cells (TPSCs) are attracting intense research interest due to their excellent optoelectric properties and eco‐friendly features. To further improve the device performance, developing new fullerene derivatives as electron transporter layers (ETLs) is highly demanded. Four well‐defined regioisomers (trans‐2, trans‐3, trans‐4, and e) of diethylmalonate‐C60 bisadduct (DCBA) are isolated and well characterized. The well‐defined molecular structure enables us to investigate the real structure‐dependent effects on photovoltaic performance. It is found that the chemical structures of the regioisomers not only affect their energy levels, but also lead to significant differences in their molecular packings and interfacial contacts. As a result, the devices with trans‐2, trans‐3, trans‐4, and e as ETLs yield efficiencies of 11.69%, 14.58%, 12.59%, and 10.55%, respectively, which are higher than that of the as‐prepared DCBA‐based (10.28%) device. Notably, the trans‐3‐based device also demonstrates a certified efficiency of 14.30%, representing one of the best‐performing TPSCs. Abstract : Structure‐dependent effects of the four fullerene bisadduct regioisomers on the device performance of tin‐based perovskite solar cells are systemically investigated. Benefiting from the favorable molecular packing, energy level alignment, and interfacial interaction, the trans‐3‐based devices yield a champion efficiency of 14.58% with a certified efficiency of 14.30%, representing one of the best‐performing tin‐based devices.